2015
DOI: 10.1016/j.ijheh.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Exposure misclassification due to residential mobility during pregnancy

Abstract: To meaningfully explore the subtle associations between environmental exposures and health, consideration must be given to error introduced by residential mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…This limitation is addressable in future pregnancy cohort studies by retrospective assessment of residential histories at recruitment. In some settings, residential histories can be more objectively ascertained via linkage to national health surveillance systems 26 . However, these systems tend to record residential location at the time of health service contact, not the time of the move.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limitation is addressable in future pregnancy cohort studies by retrospective assessment of residential histories at recruitment. In some settings, residential histories can be more objectively ascertained via linkage to national health surveillance systems 26 . However, these systems tend to record residential location at the time of health service contact, not the time of the move.…”
Section: Discussionmentioning
confidence: 99%
“…In a New York cohort, whole pregnancy exposure to particulate matter with aerodynamic diameter ≤10 μm (PM 10 ) was essentially unchanged when based on residence recorded by maternal interviews (20.11 μg.m −3 ) compared to that based on the residential location recorded at delivery (20.09 μg.m −3 ) 5 . In a UK cohort, annual PM 10 derived using the residential location at delivery was highly correlated with that derived using residential locations throughout pregnancy (Pearson r=0.88) 10 . In contrast, in another study, estimated PM 10 exposure based on address at delivery compared to complete residential history differed by more than one standard deviation in 16% of pregnancies 10 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies examining residential mobility found relatively high agreement between prenatal air pollution exposure estimates calculated using this method and estimates using complete residential history data. 1, 3, 13 One of these studies found little impact of not accounting for this mobility on effect estimates. 1 However, the geographic resolution of assigned air pollution exposure in these studies varied substantially, ranging from 1 to 19,968 square kilometers (km), and the spatial resolution of pollutant concentrations is a major determinant of the impact of residential mobility on assigned exposure.…”
Section: Introductionmentioning
confidence: 99%
“…However, such measures lack information regarding cumulative environmental exposures at the individual level. Thus, reliance on these measures as proxy for cumulative environmental exposure can result in exposure misclassification [13]. …”
Section: Introductionmentioning
confidence: 99%